Pembelajaran Biologi dengan Menggunakan Model Predict Observe Explain Terhadap Hasil Belajar Kognitif Siswa - Nining Nuraida Ning; Devie Novallyan; Intan Kartika Shary (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2022)
The purpose of this study is to investigate whether or not teaching biology to students at SMAN 2 Merangin using the Predict Observe Explain learning model has an effect on the cognitive learning outcomes of students. This study employs a One-Group Preetest-Posttest Design with a quantitative pre-experimental methodology. Total sampling was used, which means that all students in class X IPA 1 which amounted to 22 people were included in the research sample. Learning outcomes were assessed with a 30-question multiple-choice test used as the research instrument. Students' cognitive learning outcomes were calculated by means of a pre-test score of 77.87, a mean post-test score of 81.96, and a significance value of 0.000) <0.05 using a t-test. If the Effect Size is considered to be 0.00 or 50%, then the results show that H_a is accepted and H_o is rejected. That is, the Predict Observe Explain Learning Model has an effect on the cognitive domain of biology learning outcomes for class X IPA 1 SMAN 2 Merangin